In-phase and out-of-phase mixed mode loading: Investigation of fatigue crack growth in SEN specimen due to tension–compression and torsional loading. (August 2020) - Köster, Paul; Benz, Christopher; Heyer, Horst; Sander, Manuela
Highlights: Experiments at in-phase and out-of-phase tension–compression and torsional loading. Influence of the phase shift, load ratio and stress ratio on the crack propagation. Evaluation of the surface crack path on the specimen's surface using DIC. Investigation of existing mixed mode concepts by numerical simulations. Abstract: Numerous cases of damage by fatigue in structures are related to mechanical stresses due to mixed mode loading conditions. To prevent such cases of failure a precise knowledge of the corresponding theoretical background is indispensable. Unfortunately, it is not yet possible to satisfactorily describe the crack propagation by considering a superposition of all three crack modes. For this purpose, experiments on single-edge notched specimens made of 34CrNiMo6 under tension-torsion with different mixed mode ratios and phase shift angles were performed. The focus of the investigations is especially on the kinking and the twisting angle of the crack as well as on the influence on the residual lifetime. Furthermore, existing concepts concerning the prediction of the crack growth under mixed mode are evaluated.